Advances in Understanding Leishmania Pathobiology: What Does RNA-Seq Tell Us? - Salloum, Tamara; Tokajian, Sima; Hirt, Robert P. (Frontiers in Cell and Developmental Biology, 2021)
Leishmaniasis is a vector-borne disease caused by a protozoa parasite from over 20 Leishmania species. The clinical manifestations and the outcome of the disease vary greatly. Global RNA sequencing (RNA-Seq) analyses emerged as a powerful technique to profile the changes in the transcriptome that occur in the Leishmania parasites and their infected host cells as the parasites progresses through their life cycle. Following the bite of a sandfly vector, Leishmania are transmitted to a mammalian host where neutrophils and macrophages are key cells mediating the interactions with the parasites and result in either the elimination the infection or contributing to its proliferation. This review focuses on RNA-Seq based transcriptomics analyses and summarizes the main findings derived from this technology. In doing so, we will highlight caveats in our understanding of the parasite’s pathobiology and suggest novel directions for research, including integrating more recent data highlighting the role of the bacterial members of the sandfly gut microbiota and the mammalian host skin microbiota in their potential role in influencing the quantitative and qualitative aspects of leishmaniasis pathology.